Implementation of Unconstrained Chair-Type Smart Health Management Monitoring System - Yun Seo, Ji; Hong Noh, Yun; Un Jeong, Do (International Journal of Engineering and Technology, 2018)
Modern people spend many hours of daily life, such as study and work, to the sitting position with chairs and sofas.Â  If you sit for a long time with a wrong posture, musculoskeletal system disorder can occur and distraction due to low concentrations. In this research, we implemented the chair-type smart health management monitoring system which provides the user with the traditional functions of the chair more effectively and also enables various health management functions. For this reason Three load cells (SB S - beam load cell, 100 kgf) were arranged in an equilateral triangle shape between the top plate and the lower plate of the chair to construct a control section. In addition, we designed a measuring section composed of a filter and an amplifier so that we can simultaneously measure weight signal and BCG. We implemented an information-based posture discrimination algorithm of weight information and a distraction estimation method and implemented a PC and Android-based smartphone monitoring system. We conducted two experiments to evaluate the performance of the implemented system. First of all, in order to evaluate the performance of the posture discrimination algorithm, nine postures were obtained for 10 test subjects in an arbitrary order. As a result of comparing arbitrary posture and posture discrimination results, it showed discrimination performance of 97.9%. Finally, experiment was conducted to confirm the usefulness of the discrimination of distraction in daily life. The experimenter checked the change of the indicator according to the posture change during audiovisual data appreciation. Distraction continued changing posture as a result of confirming the image of the section where the numerical value is high, and confirmed that it is not concentrating on the image. The implement system can help not only health care function in daily life, but also to induce proper posture and improve sitting habit. In future studies, we intend to conduct a research to objectively demonstrate the usefulness of the Distraction estimated index.Â